Population structure, distribution pattern and habitat utilization of Yellow-wattled Lapwing, Vanellus malabaricus (Boddaert, 1783), in Northern India - Prateek; Himanshu Mishra; Vikas Kumar; Ashish Kumar (BMC Zoology)
Abstract This field study investigated the population structure, distribution pattern and habitat utilization of Yellow-wattled Lapwings. The line transect method was used to estimate the density of Yellow-wattled Lapwings. An average of 394 individuals including 77 chicks of Yellow-wattled Lapwings have been registered with an average density of 38 birds per km. The outcome of the GLM analysis exhibited, that Bakshi Ka Talab had the highest lapwing count while, Malihabad had the lowest lapwing count. A significant lapwing count in the year 2021 was confirmed. The winter season had the lowest lapwing counts, whereas the summer season had the highest values. Moreover, the largest lapwing counts were estimated in uncultivated while, the lowest lapwing count was documented in river habitat types. There was a significant difference in the mean flock size across the seasons and the habitat types. Being sighted in flocks of various sizes the distribution pattern was found to be clumped in Yellow-wattled Lapwings. The results of the factorial ANOVA showed a significant difference in the habitat utilization of Yellow-wattled Lapwings across study sites, years, seasons and habitat types. Uncultivated habitat types were the most utilized habitat types during summer seasons.